New PPAR alpha/gamma/delta Optimal Activator Rationally Designed by Computational Methods - Padilha, Elias C. [UNESP]; Serafim, Rodolfo B.; Sarmiento, Deisy Y. R.; Santos, Cesar F.; Santos, Cleydson B. R.; Silva, Carlos H. T. P. (Soc Brasileira Quimica, 2016)
The peroxisome proliferator-activated receptor gamma (PPAR gamma) is a nuclear receptor that acts as a transcription factor, regulating glucose, lipid and inflammation signaling and it is exploited in type 2 diabetes treatment. However, the selective activation of this PPAR subtype has been linked to important adverse effects which can be mitigated through concomitant activation of PPAR alpha and PPAR delta. In this study, we proposed new PPAR gamma agonists using PharmaGist Server for pharmacophore prediction, the molecular docking was performed by GOLD (genetic optimization for ligand docking) v2.2, AutoDock 4.2 and AutoDock Vina 1.1 and QikProp v4.0 and Derek for absorption, distribution, metabolism, excretion and toxicity (ADMET) assessment. One molecule showed high predicted affinity to PPAR gamma and favorable pharmacokinetic and toxicity properties. It was then evaluated against PPAR alpha and PPAR delta and showed greater affinity to these receptors than the controls. Therefore this molecule is a promising drug lead for the development of derivatives and for the treatment of metabolic syndrome with the benefits of a PPAR pan activation.
Keywords: type 2 diabetes; PPAR pan agonist; molecular modeling; ADMET prediction